Ashwagandha in brain disorders: A review of recent developments. (15th July 2020) - Zahiruddin, Sultan; Basist, Parakh; Parveen, Abida; Parveen, Rabea; Khan, Washim; Gaurav,; Ahmad, Sayeed
Abstract: Ethnopharmacological relevance: Withania somnifera (Family: Solanaceae), commonly known as Ashwagandha or Indian ginseng is distributed widely in India, Nepal, China and Yemen. The roots of plant consist of active phytoconstituents mainly withanolides, alkaloids and sitoindosides and are conventionally used for the treatment of multiple brain disorders. Aim of the review: This review aims to critically assess and summarize the current state and implication of Ashwagandha in brain disorders. We have mainly focussed on the reported neuroactive phytoconstituents, available marketed products, pharmacological studies, mechanism of action and recent patents published related to neuroprotective effects of Ashwagandha in brain disorders. Materials and methods: All the information and data was collected on Ashwagandha using keywords "Ashwagandha" along with "Phytoconstituents", "Ayurvedic, Unani and Homeopathy marketed formulation", "Brain disorders", "Mechanism" and "Patents". Following sources were searched for data collection: electronic scientific databases such as Science Direct, Google Scholar, Elsevier, PubMed, Wiley On-line Library, Taylor and Francis, Springer; books such as AYUSH Pharmacopoeia; authentic textbooks and formularies. Results: Identified neuroprotective phytoconstituents of Ashwagandha are sitoindosides VII–X, withaferin A, withanosides IV, withanols, withanolide A, withanolide B, anaferine, beta-sitosterol, withanolide D with key pharmacological effects in brain disorders mainly anxiety, Alzheimer's, Parkinson's, Schizophrenia, Huntington's disease, dyslexia, depression, autism, addiction, amyotrophic lateral sclerosis, attention deficit hyperactivity disorder and bipolar disorders. The literature survey does not highlight any toxic effects of Ashwagandha. Further, multiple available marketed products and patents recognized its beneficial role in various brain disorders; however, very few data is available on mechanistic pathway and clinical studies of Ashwagandha for various brain disorders is scarce and not promising. Conclusion: The review concludes the results of recent studies on Ashwagandha suggesting its extensive potential as neuroprotective in various brain disorders as supported by preclinical studies, clinical trials and published patents. However vague understanding of the mechanistic pathways involved in imparting the neuroprotective effect of Ashwagandha warrants further study to promote it as a promising drug candidate. Graphical abstract: Image 1